Future wonder plant pomato - Kumar, Pardeep; Negi, Viplove; Sharma, Parveen; Raj, Desh; Rana, Shivani (Indian Horticulture, 2015)
Pomato will also create opportunities for the amateur growers to develop new crop plant series. Thus, this horticultural wonder plant may bring desirable changes in the present scenario of protected cultivation.